2019
DOI: 10.3348/kjr.2018.0757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Pathophysiological Processes Induced by an Iodinated Contrast Agent in a Diabetic Rabbit Model Using Intravoxel Incoherent Motion and Blood Oxygenation Level-Dependent Magnetic Resonance Imaging

Abstract: Objective To examine the potential of intravoxel incoherent motion (IVIM) and blood oxygen level-dependent (BOLD) magnetic resonance imaging for detecting renal changes after iodinated contrast-induced acute kidney injury (CI-AKI) development in a diabetic rabbit model. Materials and Methods Sixty-two rabbits were randomized into 2 groups: diabetic rabbits with the contrast agent (DCA) and healthy rabbits with the contrast agent (NCA). In each group, 6 rabbits underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…The BOLD images in Figure 3 show the fMRI data used in our study to evaluate renal blood oxygen content and to predict CI-AKI. Upon comparing Groups A and C (or B and D), we concluded that the renal damage is induced by CM and that the main condition is hypoxia-related oxidative stress, which has been supported in various previous experiments ( Caiazza et al, 2014 ; Wang et al, 2019 ; Kusirisin et al, 2020 ). Some clinical studies on CKD have obtained similar outcomes ( Khatir et al, 2015 ; Hirakawa et al, 2017 ; Li et al, 2019 ).…”
Section: Discussionsupporting
confidence: 79%
“…The BOLD images in Figure 3 show the fMRI data used in our study to evaluate renal blood oxygen content and to predict CI-AKI. Upon comparing Groups A and C (or B and D), we concluded that the renal damage is induced by CM and that the main condition is hypoxia-related oxidative stress, which has been supported in various previous experiments ( Caiazza et al, 2014 ; Wang et al, 2019 ; Kusirisin et al, 2020 ). Some clinical studies on CKD have obtained similar outcomes ( Khatir et al, 2015 ; Hirakawa et al, 2017 ; Li et al, 2019 ).…”
Section: Discussionsupporting
confidence: 79%
“…The limitations of the single exponential model become more apparent due to the complexity of the renal structure and function, including vascular flow, tubular flow and passive diffusion [ 11 , 12 ]. The application of IVIM has been reported in research articles on diabetic renal injury [ 9 , 13 15 ]. On this basis, our team also conducted a pilot study using IVIM to evaluate the kidneys of patients with early DN [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biotin-labeled goat anti-mouse IgG served as secondary antibody, using diaminobenzidine (DAB) as chromogenic substrate. The brownish precipitates at points of peroxidase localization were interpreted using the smart segmentation tool of ImageJ (National Institutes of Health, Bethesda, MD, USA) open-source software ( Wang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Renal hypoxia and direct nephrotoxicity of CA are the universally acknowledged causes of CIAKI. Given the well-known fact that tubular vacuolar, tubulointerstitial fibrosis, and tubular damage occur in CIAKI, the hypoxia-inducible transcription factor-1α (HIF-1α) is also highly expressed in CIAKI ( Wang et al, 2019 ). We hypothesize that DTI is able to detect pathological changes of CIAKI and determine the correlation of FA to the degree of renal pathologies and HIF-1α expression.…”
Section: Introductionmentioning
confidence: 99%